The Analysis of Project Auditing System - Yadav, Ashutosh Kumar (Journal of Trends in Computer Science and Smart Technology, 2021)
During the current trends in IT and Software industry- DevOps, the project management system is mainly responsible to keep track of various projects that are undertaken by the organization and developed with in same premises or geographically locations. The main problem is to develop a system which can handle various task of project management by providing security to project related work while transferring and to provide a communication system for discussion of problems. So this system will run on the virtual private network of organization also secured socket layer is used instead simple hypertext transfer protocol. In project management system the client wants a system that can be used to check the progress that the projects had made which it had distributed among different organization for development. In this arena a central repository (database) should be created which will be maintained by project developing origination on day-to-day basis i.e. the organization must have to update the database on the basis of progress made by them on the given module. The files will be uploaded by assigned user on any particular project about his daily work. There will be various powers to the user which will be provided according to role of a person in particular project. In this system only the status will be changed and nothing will be deleted until any particular project will be completed. Menu of different project will be shown also according to the role. Each user will be provided unique id. for a particular project however user can perform different role simultaneously.